Urban Soils - Lal, Rattan; Stewart, B. A. (Boca Raton, FL : CRC Press, 2017)
"Globally, 30% of the world population lived in urban areas in 1950, 54% in 2016 and 66% projected by 2050. The most urbanized regions include North America, Latin America, and Europe.? Urban encroachment depletes soil carbon and the aboveground biomass carbon pools, enhancing the flux of carbon from soil and vegetation into the atmosphere. Thus, urbanization has exacerbated ecological and environmental problems. Urban soils are composed of geological material that has been drastically disturbed by anthropogenic activities and compromised their role in the production of food, aesthetics of residential areas, and pollutant dynamics. Properties of urban soils are normally not favorable to plant growth$1 (Bthe soils are contaminated by heavy metals and are compacted and sealed. Therefore, the quality of urban soils must be restored to make use of this valuable resource for delivery of essential ecosystem services (e.g., food, water and air quality, carbon sequestration, temperature moderation, biodiversity). Part of the Advances in Soil Sciences Series, Urban Soils explains properties of urban soils; assesses the effects of urbanization on the cycling of carbon, nitrogen, and water and the impacts of management of urban soils, soil restoration, urban agriculture, and food security; evaluates ecosystem services provisioned by urban soils, and describes synthetic and artificial soils."--Provided by publisher.s
chapter 1 Urban Agriculture in the 21st Century -- chapter 2 Urban Soil Mapping through the United States National Cooperative Soil Survey -- chapter 3 Changes in Soil Organic Carbon Stocks by Urbanization -- chapter 4 Drivers of Urban Soil Carbon Dynamics -- chapter 5 Soil Carbon and Nitrogen Cycling and Ecosystem Service in Cities -- chapter 6 Urban Soil Carbon Storage -- chapter 7 Sealing Effects on Properties of Urban Soils -- chapter 8 Contaminants in Urban Soils: Bioavailability and Transfer -- chapter 9 Optimizing the Hydrologic Properties of Urban Soils -- chapter 10 Making Soils from Urban Wastes -- chapter 11 Properties of Soils Affected by Highways -- chapter 12 An Applied Hydropedological Perspective on the Rendering of Ecosystem Services from Urban Soils -- chapter 13 Biogeochemistry of Rooftop Farm Soils -- chapter 14 Managing Urban Soils for Food Production -- chapter 15 Vertical Farming Using Hydroponics and Aeroponics -- chapter 16 Soils and Waste Management in Urban India -- chapter 17 Enhancing Awareness about the Importance of Urban Soils -- chapter 18 Feeding Megacities by Urban Agriculture.
Keywords: Urban soils; NATURE -- Environmental Conservation & Protection; SCIENCE -- Life Sciences -- Botany; NATURE -- Ecology; NATURE -- Ecosystems & Habitats -- Wilderness; Agriculture; Ecology - Environment Studies; Soil Science; NATURE / Environmental Conservation & Protection; SCIENCE / Life Sciences / Botany